THE COMPATIBILITY OF SHARIAH LAW AND MODERN CAPITALISM: A CASE STUDY OF INDONESIA'S ISLAMIC BANKING SECTOR - Thandar Htwe; Soe Thu Zaw; Ali Reza (Sharia Oikonomia Law Journal, 2025)
The integration of Shariah law with modern capitalism has been a subject of significant debate, particularly in the context of Islamic banking. In Indonesia, the world’s largest Muslim-majority country, Islamic banking has grown rapidly, offering a unique case study to explore this compatibility. This study examines the alignment of Shariah principles with the practices of modern capitalism in Indonesia’s Islamic banking sector, focusing on issues such as profit-sharing, risk management, and ethical investment. The research aims to identify the challenges and opportunities associated with integrating Shariah law into a capitalist financial system and propose strategies for enhancing this compatibility. Using a mixed-methods approach, this study combines quantitative analysis of financial performance data with qualitative interviews with Islamic banking practitioners, Shariah scholars, and regulators. Data were analyzed to assess the adherence of Islamic banks to Shariah principles, their financial performance, and their role in promoting ethical finance. The findings reveal that while Islamic banks in Indonesia generally comply with Shariah principles, challenges such as profit-driven practices and limited product innovation hinder their full alignment with Islamic ethics. The study concludes that enhancing the compatibility of Shariah law and modern capitalism requires a balanced approach that prioritizes ethical finance while maintaining competitiveness.